A High-Accurate Time Integration Method for Solving Structural Vibration Responses. (2nd November 2022) - Lei, Xiangsheng; Wang, Yanfeng; Wang, Xinghua; Lin, Gang; Qin, Xinyan
Abstract : A time integration method for the equations of motion is developed based on the Gauss implicit Runge-Kutta method to high-accurate solving the responses in structural vibration. The present method possesses the features of unconditional stability and self-starting and can achieve fourth-order accuracy in displacement, velocity, and acceleration simultaneously. The algorithm is a matrix form and no need to iterate in the calculation. The convergent accuracy is verified by a numerical example, and the effectiveness is also verified by solving the dynamic responses of a vibration isolation system and the vibration responses of a pylon structure with cyclic loads and earthquake loads.